Respuesta :
From the four functions listed, eliminate the middle two, because neither has the constant coefficient 2.
This leaves f(x) = 2x^3 - 3 and f(x) = 2x^2 + 3x - 3.
Please note: use "^" to indicate exponentiation; do not write "x2" or "x3."
Eliminate f(x) = 2x^3-3, because it's NOT a quadratic function.
This leaves f(x) = 2x^2 + 3x - 3 as the answer; it has a leading coeff. of 2 and a constant term of -3, as required.
This leaves f(x) = 2x^3 - 3 and f(x) = 2x^2 + 3x - 3.
Please note: use "^" to indicate exponentiation; do not write "x2" or "x3."
Eliminate f(x) = 2x^3-3, because it's NOT a quadratic function.
This leaves f(x) = 2x^2 + 3x - 3 as the answer; it has a leading coeff. of 2 and a constant term of -3, as required.